2022
DOI: 10.1146/annurev-biophys-082521-113418
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin Mechanisms: Multiple and (Mis)Understood?

Abstract: The chaperonins are ubiquitous and essential nanomachines that assist in protein folding in an ATP-driven manner. They consist of two back-to-back stacked oligomeric rings with cavities in which protein (un)folding can take place in a shielding environment. This review focuses on GroEL from Escherichia coli and the eukaryotic chaperonin-containing t-complex polypeptide 1, which differ considerably in their reaction mechanisms despite sharing a similar overall architecture. Although chaperonins feature in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 142 publications
0
26
0
Order By: Relevance
“…Potential roles of bullet- and football-shaped GroEL–GroES complexes (BS- and FB-conformations, respectively) remain somewhat controversial. , Bigman suggests that BS and FB structures may coexist and that their relative activities may be linked to ATP concentrations, which have been shown to be widely variable . A more complete summary of bullet- vs football-shaped GroEL–GroES complexes can be found in a recent review by Horovitz et al…”
Section: Introductionmentioning
confidence: 99%
“…Potential roles of bullet- and football-shaped GroEL–GroES complexes (BS- and FB-conformations, respectively) remain somewhat controversial. , Bigman suggests that BS and FB structures may coexist and that their relative activities may be linked to ATP concentrations, which have been shown to be widely variable . A more complete summary of bullet- vs football-shaped GroEL–GroES complexes can be found in a recent review by Horovitz et al…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7] The equatorial domain also harbors the ATP binding site for each subunit. 1 While the structure, dynamics, and ATP binding of GroEL has been extensively investigated, [8][9][10][11][12][13][14][15][16][17][18][19][20] we recently reported results using native mass spectrometry (nMS) that reveal new insights about stability and stoichiometry of GroEL-ATP/GroES interactions. 21 Using variable-temperature electrospray ionization (vT-ESI) we found that GroEL-ATP binding was temperature and ATP-concentration dependent, indicating that the thermodynamics of this vital interaction for the GroEL nanomachine might reveal new information as to how the GroEL nanomachine operates.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Hsp70-Hsp40-Hsp110 (DnaK-DnaJ-GrpE in E coli), chaperone-assisted unfolding-refolding occurs via DnaJ-binding motives, enriched with bulky hydrophobic amino acids on the surface of misfolded structures in aggregated polypeptides (Rüdiger et al, 2001) and DnaK-binding motives, generally misfolded structures which, once unfolded, consist of five consecutive hydrophobic residues, flanked by positive charges in un-structured polypeptide segments (Rüdiger et al, 1997). In the case of Hsp60 (GroEL-GroES in E coli), chaperone-assisted unfolding-refolding occurs via cooperative binding of exposed hydrophobic surfaces on aggregation-prone misfolded polypeptides, to a ring of hydrophobic motives displayed by the apical domains of the GroEL heptameric oligomers (Horovitz et al, 2022;Priya et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%